Estimation of Neighbors Position privacy scheme with an Adaptive Beaconing approach for location privacy in VANETs. (October 2018) - Zidani, Ferroudja; Semchedine, Fouzi; Ayaida, Marwane
Abstract: In this work, we consider the issue of designing a location privacy scheme that preserve the Quality of Service (QoS) of the road safety applications. We propose a privacy mechanism, denoted Estimation of Neighbors Position privacy scheme with an Adaptive Beaconing approach (ENeP-AB), in which the change of pseudonym is based on the number of neighbors and their predicted positions. Then, we show that the Adaptive Beaconing approach, used to manage efficiently the wireless channel and to provide reliable vehicular communications, guarantees the same performances in terms of location privacy as well as the radio silence technique. Hence, the proposed privacy scheme is extended with an Adaptive Beaconing approach, called Extended Adaptive Beaconing Rate Protocol (E-ABRP). Our simulations demonstrate clearly that the beaconing rate approaches create a confusion in location and time where the change of pseudonym occurs while improving the quality of safety applications.